Maternal mortality in the municipality of Rio de Janeiro between the years 2015 and 2019: a retrospective study (Research, Society and Development, 2020)
Introduction: maternal mortality is a public health problem worldwide. Objective: to describe the epidemiological profile of maternal mortality in the city of Rio de Janeiro between the years 2015 to 2019. Methodology: a descriptive and retrospective study carried out by collecting secondary data from the Mortality Information System (SIM) and the Live Birth Information System (Sinasc), available through the public access website of the Informatics Department of the Unified Health System Health (Datasus). The maternal mortality ratio and the proportions of sociodemographic variables and the basic causes of deaths were calculated. Data were allocated and analyzed using tabwin and Microsoft Excel software. Results: there were 571 maternal deaths of residents of the municipality of Rio de Janeiro, 46% (N = 263) of deaths classified as late being excluded in this study, thus analyzing 308 maternal deaths. The maternal mortality ratio was higher in the program area (AP) 5.3, followed by AP 3.3. Maternal deaths predominated in single women (65.3%), aged 30 to 39 years (40.6%), brown (47.1%), with 4 to 7 years of schooling (41.6%) and “home” (40.9%). The highest proportion of deaths analyzed was due to direct causes (60.4%). Among these types of causes, the most evident were hemorrhagic syndromes, hypertensive disorders, puerperal infection, embolism and abortion. Conclusion: the results of this study showed a scenario characterized by high maternal mortality in the city of Rio de Janeiro, reaching pregnant women and women in the poorest areas.